A Bridge Too Far?: commonalities and differences between China and the United States - Grafstein, Robert; Wen, Fan (Lexington Books, 2009)
Can China and the United States bridge their political differences? Are those differences as large as conventional wisdom suggests? Thirty years after formal U.S.-Chinese diplomatic relations were established, A Bridge Too Far? addresses these essential questions by bridging the academic divide separating scholars who study these countries from Chinese and Western political science perspectives. Rather than bringing together China specialists exclusively, then, this book allows a broad range of scholars using Western analytical tools to examine Chinese politics and political theory in relation to the United States. It also allows Chinese scholars to examine specific policy areas related to countries and thereby confirm or contest the broader analysis offered by their outsider counterparts. Some of the contributors are Chinese specialists, a number having played key roles as advisors to the central government, others students of American politics, and stilll others political economists or political theorists who are not involved directly in area studies. Finally, some are academically trained but work in China in the area of environmental regulation or are legal advisors for state-owned businesses. In all, the contributors bring extensive experience with China, and all see commonalities beneath the obvious and deep differences between the two nations. Emerging from an ongoing face-to-face dialog, the book unites this unusual group to uncover genuine areas of overlap between the politics of the two nations without diminishing the very real distance separating them. The essays included discuss topics such as China's democratic prospects and the rise of local village elections, the role of interest groups, Chinese political and legal reforms and developments regarding intellectual property rights and environmental regulation, Western and Chinese political philosophy, and Sino-American foreign policy interactions.